Congenital Thrombasthenia In Children Welfare Teaching Hospital: A Descriptive Study - Hussaia, Lubna Foad; Abid, Obeida Amir (AL-Kindy College Medical Journal, 2016)
Background: Thrombasthenia is an inherited genetic disorder affecting platelets, which is characterized by spontaneous muco-cutaneous bleeding and abnormally prolonged bleeding in response to injury or trauma. Objectives: The aim of this study was to assess the diagnosis and treatment of thrombasthenia in Children Welfare Teaching Hospital. Type of the study: A cross-sectional study. Methods: This descriptive study was performed on 66 patients with thrombasthenia from the first of October 2013 till the first of July 2015.The diagnosis of the disease was done by a wide spectrum of characteristics including family history, clinical manifestations, laboratory tests.. Results: The common manifestations of the disease at time of diagnosis were epistaxis in 23 patients (34.8%) and gum bleeding in 22 patients (33.3%) .Mostly established at age 1-10years.Family history was positive in most patients.hepatitis C was rare in our patients after platelet transfutions. Conclusions: : It is a rare hemorrhagic disease in our center, mostly presented as minor bleeding involving mainly mucocutaneous regions which appears at an early childhood with positive family history in most cases